Gd‐EOB‐DTPA‐enhanced magnetic resonance imaging and alpha‐fetoprotein predict prognosis of early‐stage hepatocellular carcinoma. Issue 5 (29th September 2014) - Yamashita, Taro; Kitao, Azusa; Matsui, Osamu; Hayashi, Takehiro; Nio, Kouki; Kondo, Mitsumasa; Ohno, Naoki; Miyati, Tosiaki; Okada, Hikari; Yamashita, Tatsuya; Mizukoshi, Eishiro; Honda, Masao; et al.
<x xml:space="preserve">Abstract</x> The survival of patients with hepatocellular carcinoma (HCC) is often individually different even after surgery for early‐stage tumors. Gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd‐EOB‐DTPA)‐enhanced magnetic resonance imaging (MRI) has been introduced recently to evaluate hepatic lesions with regard to vascularity and the activity of the organic anion transporter OATP1B3. Here we report that Gd‐EOB‐DTPA‐enhanced MRI (EOB‐MRI) in combination with serum alpha‐fetoprotein (AFP) status reflects the stem/maturational status of HCC with distinct biology and prognostic information. Gd‐EOB‐DTPA uptake in the hepatobiliary phase was observed in ∼15% of HCCs. This uptake correlated with low serum AFP levels, maintenance of hepatocyte function with the up‐regulation of OATP1B3 and HNF4A expression, and good prognosis. By contrast, HCC showing reduced Gd‐EOB‐DTPA uptake with high serum AFP levels was associated with poor prognosis and the activation of the oncogene FOXM1. Knockdown of HNF4A in HCC cells showing Gd‐EOB‐DTPA uptake resulted in the increased expression of AFP and FOXM1 and the loss of OATP1B3 expression accompanied by morphological changes, enhanced tumorigenesis, and loss of Gd‐EOB‐DTPA uptake in vivo. HCC classification based on EOB‐MRI and serum AFP levels predicted overall survival in a single‐institution cohort (n = 70), and its prognostic utility was validated independently in a multi‐institution cohort of early‐stage HCCs (n = 109). Conclusion: This noninvasive classification system is molecularly based on the stem/maturation status of HCCs and can be incorporated into current staging practices to improve management algorithms, especially in the early stage of disease. (Hepatology 2014;60:1674–1685)